Attitudes and factors influencing organ donation decision-making in Damascus, Syria: a cross-sectional study - Soqia, Jameel; Ataya, Jamal; Alhomsi, Rawan; Soqia, Horiya; Kakaje, Ameer; Saadoun, Rakan; Hamzeh, Ammar (Scientific reports, 2023)
Organ donation is vital to saving lives, but its success depends on people's willingness to donate organs. This descriptive cross-sectional survey aimed to investigate attitudes towards organ donation in Damascus, Syria. Understanding attitudes is crucial for the success of organ donation programs, especially in countries with similar settings. This study was a descriptive cross-sectional survey aimed at understanding patients’ attitudes towards organ donation in Damascus, Syria. Data was collected through a carefully constructed validated survey through face-to-face interviews. 600 participants were randomly interviewed, 62.8% agreed to donate their organs after death, with helping others being the primary reason. Religious beliefs were the primary reason for organ refusal in males, while for females, it was lack of knowledge and religious beliefs. However, there were no significant differences between genders or educational level and age groups in the acceptance of organ donation. The percentage of those who agree to donate their organs after death encourages taking an effective step to build an integrated donation system, not just a center. Bearing in mind that there is no correlation with age, gender or even educational level, which means that the system may include different groups of society.